Angiogenesis and epidermal growth factor receptor inhibitors in non-small cell lung cancer - Giuliano Palumbo; Giovanna Esposito; Guido Carillio; Anna Manzo; Agnese Montanino; Vincenzo Sforza; Raffaele Costanzo; Claudia Sandomenico; Carmine La Manna; Nicola Martucci; Antonello La Rocca; Giuseppe De Luca; et al. (Open Exploration Publishing Inc., 2020)
Several preclinical studies suggested a potential benefit from combined treatment with inhibitors of epidermal growth factor receptor (EGFR) and angiogenesis, both effective in patients with advanced non-small-cell lung cancer (NSCLC). In pretreated patients with advanced EGFR wild type NSCLC, bevacizumab plus erlotinib improved progression-free survival as second-line therapy in the BeTa study and as maintenance therapy in the ATLAS trial, although the benefit was modest and did not translate into an advantage in overall survival. Disappointing results were reported with oral VEGF inhibitors plus erlotinib in pretreated patients with EGFR wild type NSCLC. On the contrary, erlotinib plus bevacizumab or ramucirumab showed a clinically relevant improvement of progression-free survival in naïve patients with EGFR mutations, leading to the approval of these two regimens as first-line treatment of NSCLC patients with EGFR mutant tumors. Several clinical studies are evaluating the feasibility and activity of osimertinib plus bevacizumab or ramucirumab. However, limits that could affect its use in clinical practice are the need of an intravenous infusion for angiogenesis inhibitors, the increased incidence of treatment associated adverse events, the exclusion of patients with tumors located in central position or at risk of hemorrhage. The identification of predictive biomarkers is an important goal of research to optimize the combined use of these agents.